Complement levels and risk of organ involvement in patients with systemic lupus erythematosus. Issue 1 (25th June 2017) - Gandino, Ignacio Javier; Scolnik, Marina; Bertiller, Emmanuel; Scaglioni, Valeria; Catoggio, Luis Jose; Soriano, Enrique Roberto
Abstract : Objective: Complement plays a major role in SLE. Complement participation has been linked to disease activity and damage. Our objective was to estimate the association of complement behaviour with clinical manifestations, visceral injury and mortality in patients with SLE. Methods: Complement determinations (C3 and C4 levels) were analysed in patients with SLE (fulfilling American College of Rheumatology (ACR) or Systemic Lupus International Collaborating Clinics (SLICC)criteria) seen at a university hospital between 2000 and 2013. Patients were grouped in those with permanent C3 and/or C4 low values (low complement group), those with C3 and C4 constant normal values (normal complement group) and those with fluctuant values (periods of normal and periods of low values: fluctuant group). Clinical characteristics and mortality were analysed and compared between groups. Results: 270 patients with SLE were included (242 females, 89.6%), mean age at diagnosis was 34.2 years (SD 15.8). 75 patients had fluctuant levels of complement, 79 patients had persistent low complement levels and 116 had normal complement levels. Lupus glomerulonephritis was more frequent in patients with fluctuant levels (75%, 56% and 49%, respectively, p=0002). The normal complement group had less frequency of haematological involvement and anti-double stranded DNA (dsDNA) antibodies. At the end of the follow-up, 53% of the patients had damage (SLICC/ACR ≥1). In a Cox proportional hazard model age at diagnosis, neurological impairment, thrombocytopaenia and corticosteroids were associated with more damage, while hydroxychloroquine was a protective factor. There were no differences between complements groups on accumulated damage. Ten-year survival rate was 93%, 93.5% and 92% for the normal complement group, the persistently low group and the fluctuant group, respectively. Conclusions: Patients with constant normal complement had lower prevalence of haematological involvement and anti-dsDNA, while patients with fluctuant complement had higher renal impairment. Neither the persistent low complement nor the fluctuant complement groups had increased mortality and/or visceral damage.